A Review on Vertical Take-Off and Landing (VTOL) Tilt-Rotor and Tilt Wing Unmanned Aerial Vehicles (UAVs). (29th September 2022) - Misra, Akshat; Jayachandran, Sudhakaran; Kenche, Shivam; Katoch, Anirudh; Suresh, Arjun; Gundabattini, Edison; Selvaraj, Senthil Kumaran; Legesse, Addisalem Adefris
Abstract : The Vertical Take-off and Landing (VTOL) unmanned aerial vehicles (UAVs) with the tilt-rotor mechanism also known as hybrid UAVs have a lot of challenges in designing and controlling concerning their use in harsh weather for surveillance and access to remote areas. This review paper presents a review of the preliminary design of hybrid aircraft and control systems. The tilt-rotor mechanism and tilt wings of a hybrid UAV are analyzed. The paper provides an outline of technical advances in UAVs in hybrid configuration concerning their constraint analysis, propulsion sizing, and design evaluation. Furthermore, the flight dynamics modeling is described with the control system and dynamics of the hybrid UAV. This paper lists various software for simulations and analysis such as SOLIDWORKS and CATIA for CAD modeling, MATLAB and SIMULINK for mathematical modeling and flight control, and XFLR5 for stability analysis of aerofoils, wings, and planes. In addition, certain control strategies are executed and scrutinized in terms of the theory, the linearity, and the implementation of the model.